1991
DOI: 10.1001/archsurg.1991.01410300110017
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Invasive Procedures in Therapy for Primary and Secondary Spontaneous Pneumothorax

Abstract: Timing of invasive procedures during chest tube therapy in spontaneous pneumothorax is undefined. Evaluation of 115 patients with primary and secondary spontaneous pneumothorax treated with tube thoracostomy revealed nearly maximal healing rates after 48 hours without a relevant increase if drainage was maintained for up to 10 days. In secondary spontaneous pneumothorax, a significantly lower healing rate was observed after 48 hours compared with primary spontaneous pneumothorax (60% vs 82%). Therapeutic succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
3
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 7 publications
4
74
3
5
Order By: Relevance
“…These suggestions are, at best, expert-based, with little or no supporting evidence. Schoenenberger et al 4 recorded healing rates of 82% in primary and 60% in secondary spontaneous pneumothorax at 48 hr, with little increase in the number that healed in the next 8 days however this study included only adults, and may represent a different underlying illness with a different natural history from a pediatric population.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…These suggestions are, at best, expert-based, with little or no supporting evidence. Schoenenberger et al 4 recorded healing rates of 82% in primary and 60% in secondary spontaneous pneumothorax at 48 hr, with little increase in the number that healed in the next 8 days however this study included only adults, and may represent a different underlying illness with a different natural history from a pediatric population.…”
Section: Introductionmentioning
confidence: 93%
“…34 Several authors have quoted their own definition of a ''persistent air leak'' and the point at which they would consider progression to an invasive surgical procedure (Table 1). [3][4][5][6][7][8][9] Reviews of series of adult patients have suggested delaying surgical intervention for 5-10 days, in contrast to reviews of younger patients that have urged early intervention. These suggestions are, at best, expert-based, with little or no supporting evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the indication for surgery in pneumothorax patients is decided during drainage. 7,10) Using outpatient drainage therapy, this decision can be made on an outpatient basis.…”
Section: Discussionmentioning
confidence: 99%
“…As to extending the indication for immediate VATS intervention to patients presenting their first episode of SP, this is feasible with surgeons familiar with this procedure (Hatz et al, 2000;Torresini et al, 2001;Connolly et al, 2002). Nearly half of patients with first-time SP at some time require an operation either because of the persistent air leakage or later recurrence (Schoenenberger et al, 1991). Thus, chest CT evaluation is valuable because VATS for patients with a first-attack SP will be more strongly indicated if bullae or blebs are visible.…”
Section: Discussionmentioning
confidence: 99%